Glossary of Evaluation Terminology (Urdu- English- Urdu) - (:unkn) unknown (My University, 2013)
The 'Glossary' provides equivalents in Hindi/Kannada/Tamil/Urdu for about 1000 evaluation terms in English. The 'Introduction' provides a brief explanatory note on each of these concepts.
Keywords: Urdu; English